2014
DOI: 10.1108/wjemsd-05-2013-0030
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial orientation and performance: the interaction effect of customer capital

Abstract: Purpose – The purpose of this study is to advance research on entrepreneurial orientation (EO), resource-based view (RBV), customer (relational) capital, and small and medium enterprises (SMEs) by examining how the interaction effect of customer capital shapes the relationship between EO and firm performance. Design/methodology/approach – This research is considered as a correlational rather than a casual study with 150 questionnaire ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 108 publications
7
61
0
7
Order By: Relevance
“…Innovation-oriented activities can affect the SME's performance, meaning that the higher the level of innovation undertaken by SMEs performance will further encourage the improvement of the SME's performance. This finding is consistent with several previous studies showing that the level of innovation has a positive and significant effect on company performance (Jalali, 2014); (Mason, 2015). This finding says that there is a positive and significant effect on entrepreneurial orientation on SME's performance.…”
Section: The Effect Of Entrepreneurship Orientation On the Smes Perfosupporting
confidence: 93%
“…Innovation-oriented activities can affect the SME's performance, meaning that the higher the level of innovation undertaken by SMEs performance will further encourage the improvement of the SME's performance. This finding is consistent with several previous studies showing that the level of innovation has a positive and significant effect on company performance (Jalali, 2014); (Mason, 2015). This finding says that there is a positive and significant effect on entrepreneurial orientation on SME's performance.…”
Section: The Effect Of Entrepreneurship Orientation On the Smes Perfosupporting
confidence: 93%
“…Despite the results of previous studies finding a negative relationship between risk-taking and performance, entrepreneurs generally accept that entrepreneurship involves risk-taking; thus, they are willing to take risks in return for potential rewards (Gebreegziabher & Tadesse, 2014;Jalali et al, 2014;Segal, Borgia, & Schoenfeld, 2005). Furthermore, Mc Clelland (1961) argues that entrepreneurs are more eager to take risks than non-entrepreneurs.…”
Section: Risk-taking and Performancementioning
confidence: 55%
“…Jalali et al (2014) found that a firm's customer capital enables Iranian entrepreneurs to develop proactive and risk-taking capabilities resulting in greater profitability. Our results suggest that Iranian entrepreneurs who cultivate different type of ties simultaneously are more likely to perform better.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, there is a significant positive relationship between IC and CA (r = 0.35, p < 0.01) as well as a significant positive relationship between ES and NVP (r = 0.29, p < 0.01). The correlation values between all the factors less than 0.80 indicate that there is no multicollinearity issue (Jalali, Jaafar, & Ramayah, 2014). …”
Section: Correlationmentioning
confidence: 99%